Enzymatic Activity Analysis and Catalytic Essential Residues Identification of Brucella abortus Malate Dehydrogenase - Xiangan Han; Yongliang Tong; Mingxing Tian; Yuxi Zhang; Xiaoqing Sun; Shaohui Wang; Xusheng Qiu; Chan Ding; Shengqing Yu (The Scientific World Journal)
Malate dehydrogenase (MDH) plays important metabolic roles in bacteria. In this study, the recombinant MDH protein (His-MDH) of Brucella abortus was purified and its ability to catalyze the conversion of oxaloacetate (OAA) to L-malate (hereon referred to as MDH activity) was analyzed. Michaelis Constant (Km) and Maximum Reaction Velocity (Vmax) of the reaction were determined to be 6.45×10−3 M and 0.87 mM L−1 min−1, respectively. In vitro studies showed that His-MDH exhibited maximal MDH activity in pH 6.0 reaction buffer at 40°C. The enzymatic activity was 100%, 60%, and 40% inhibited by Cu2+, Zn2+, and Pb2+, respectively. In addition, six amino acids in the MDH were mutated to investigate their roles in the enzymatic activity. The results showed that the substitutions of amino acids Arg 89, Asp 149, Arg 152, His 176, or Thr 231 almost abolished the activity of His-MDH. The present study will help to understand MDH’s roles in B. abortus metabolism.